Effectiveness of Use the Financial Application to Solve the Problem of MSMEs: Small and Medium Micro Businesses) at UD Maragordong HRP - Harahap, Nur Hasanah; Kamilah (As-Syirkah: Islamic Economic & Financial Journal, 2022)
The challenges of Micro, Small and Medium Enterprises are increasingly diverse in this digitalization era, classic and basic problems cannot be solved such as Lack of Experience, Access to Consumers and Capital. Basically, Micro, Small and Medium Enterprises are the nation's economic shield in the midst of a crisis and are able to absorb almost all of the workforce. However, through digitization and the use of the 'book stall' application, it is hoped that it can describe problems for business actors such as recording for business actors who are less experienced and can access the market so that they can cover up these classic problems. With this digitalization, the work of business actors is also of higher quality and improves the professionalism of business actors.